Bone Cells Dynamics during Peri-Implantitis: a Theoretical Analysis - Maria Helena Fernandes; Pedro de Sousa Gomes (Stilus Optimus, 2016)
Objectives: The present manuscript aims a detailed characterization of the bone cells dynamics during physiological bone remodelling and, subsequently, to address the cellular and molecular mechanisms that play a fundamental role in the immune-inflammatory-induced uncoupled bone remodelling observed in peri-implantitis. Results: An intimate relationship between the immune system and bone is acknowledged to be determinant for bone tissue remodelling and integrity. Due to the close interaction of immune and bone cells, the two systems share a number of surface receptors, cytokines, signalling pathways and transcription factors that are involved in mutual regulatory mechanisms. This physiological equilibrium is disturbed in pathological conditions, as verified in peri-implantitis establishment and development. Activation of the innate and adaptive immune response, challenged by the local bacterial infection, induces the synthesis of high levels of a variety of pro- and anti-inflammatory cytokines that disturb the normal functioning of the bone cells, by uncoupling bone resorption and formation, ending up with a net alveolar bone loss and subsequent implant failure. Most data points to an immune-inflammatory induced osteoclast differentiation and function, as the major underlying mechanism to the uncoupled bone resorption to bone formation. Further, the disturbed functioning of osteoblasts, reflected by the possible expression of a fibro-osteoblastic phenotype, may also play a role. Conclusions: Alveolar bone loss is a hallmark of peri-implantitis. A great deal of data is still needed on the cellular and humoral crosstalk in the context of an integrated view of the osteoimmunologic interplay occurring in the peri-implantitis environment subjacent to the bone loss outcome.